Analysis of clinicopathological risk factors for locoregional recurrence of oral squamous cell carcinoma – Retrospective analysis of 517 patients. Issue 10 (October 2017) - Safi, Ali-Farid; Kauke, Martin; Grandoch, Andrea; Nickenig, Hans-Joachim; Zöller, Joachim E.; Kreppel, Matthias
Abstract: Introduction: Recurrence is one of the main reasons for poor prognosis of OSCC. The mortality rate is approximately 90% and the 5-year overall survival rate decreases from 90% to 30% when recurrence is diagnosed. Identification of clinicopathological risk factors predicting recurrence may be helpful for patient individualized management and improvement of therapy. Therefore we investigated in our study the incidence of locoregional recurrences and their association with clinicopathological factors to identify possible significant risk factors. Material and methods: Our retrospective study consisted of 517 patients, who were diagnosed and treated between 2003–2013 at the Department for Oral and Maxillofacial Plastic Surgery, University of Cologne. Inclusion criteria were patients with treatment naive oral squamous cell carcinoma and primarily curative intended surgery with negative resection margins. Contingency tables and χ 2 -test were performed to analyse associations between clinicopathological features and recurrence. Multivariate analysis was performed using binary logistic regression analysis. Results: We found out a significant correlation in univariate analysis between locoregional recurrence and number of resected cervical lymph nodes ( p = 0.013), number of positive cervical lymph nodes ( p = 0.041), postoperative radiatio ( p = 0.018), extracapsular spread ( p = 0.028) as well as grading ( p = 0.016). In multivariate analysis only grading was shown as independent risk factor for recurrence. Conclusions: Histological grading has been demonstrated as an independent risk factor for locoregional recurrence in the multivariate analysis. Furthermore, univariate analysis indicated the number of resected and positive lymph nodes, postoperative radiatio and extracapsular spread as significant risk factors. Taking these results into account, the mentioned parameters, especially histological grading, need to be considered for an individualized therapy management of patients with OSCC.